Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Detection of signature double-negative T cells is a predictive marker to identify autoimmune lymphoproliferative syndrome associated with FAS loss of function - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Dell'Orso, Gianluca; Aigner, Michael; Fecker, Gisela; Hinze, Claas; Wittkowski, Helmut; Bruns, Heiko; Zierk, Jakob; Metzler, Markus; et al. (American Journal of Hematology, 2024)
CRIS-Team Scopus Importer:2024-03-29

Detection of Signature Double-Negative T Cells Is a Reliable Marker for ALPS Associated with FAS Mutation - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Terranova, Paola; Hinze, Claas; Aigner, Michael; Wittkowski, Helmut; Bruns, Heiko; Ehl, Stephan; Metzler, Markus; Arkwright, Peter; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Severity of COVID-19 disease is related to hyperactivation and altered migratory capacity of T cells - Spörl, Silvia; Kremer, Anna-Lena; Aigner, Michael; Eisenhauer, Nina; Koch, P.; Meretuk, L.; Loeffler, P.; Lutzny-Geier, Gloria; Vetter, Marcel; Bruns, Heiko; Mackensen, Andreas; Kremer, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Single-cell Transcriptome Analysis and clonal Kinetics in a Patient after CD19.CAR-T Cell Therapy - Lischer, Christopher; Eisenhauer, Nina; Aigner, Michael; Jacobs, Benedikt; Schletter, M.; Gebhard, C.; Rehli, M.; Bruns, Heiko; Müller, Fabian; Mackensen, Andreas; Vera González, Julio; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07